Dynamics of Law Enforcement of Illegal Online Loan Cases in Indonesia - Dermawan, Rahmat (Journal of Law and Humanity Studies, 2024)
The rise of illegal online lending cases in Indonesia has caused various negative impacts on the community, including intimidation in collection, misuse of personal data, and unreasonable interest rates. Although the government has issued various regulations and blocked illegal platforms, law enforcement against illegal loan actors still faces various obstacles, such as the difficulty of tracking down perpetrators based abroad and the lack of coordination between relevant institutions. This study aims to analyze the dynamics of law enforcement against illegal lending cases in Indonesia, by reviewing the effectiveness of regulations that have been implemented, challenges in policy implementation, and strategies that can be adopted to improve legal protection for victims of illegal loans. The method used in this study is a literature study with a systematic literature review (SLR) approach, in which various academic sources, policy reports, and laws and regulations are analyzed to understand trends and challenges in law enforcement against illegal loans. The results of the study show that despite various policies and law enforcement measures, the existence of illegal online loans is still difficult to eradicate comprehensively. Some of the factors that hinder the effectiveness of law enforcement are regulatory gaps, low public financial literacy, and weak international cooperation in eradicating illegal platforms that operate across borders. Therefore, a more comprehensive strategy is needed, including increased coordination between institutions, the application of more sophisticated technology in tracking perpetrators, and public education to increase awareness of the risks of illegal online loans.